2004
DOI: 10.1152/ajpregu.00268.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selective deficits in the circadian light response in mice lacking PACAP

Abstract: Previous studies indicate that light information reaches the suprachiasmatic nucleus through a subpopulation of retinal ganglion cells that contain both glutamate and pituitary adenylyl cyclase-activating peptide (PACAP). Although the role of glutamate in this pathway has been well studied, the involvement of PACAP and its receptors is only beginning to be understood. To investigate the functions of PACAP in vivo, we developed a mouse model in which the gene coding for PACAP was disrupted by targeted homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
110
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 34 publications
15
110
3
Order By: Relevance
“…Using the type II procedure, we found that the response to light stimulation in PAC1 KO mice differed from our previously obtained results using the type I regime (11). Most striking was the attenuated phase delay found in the type II at early night (increased in type I), a result, however, which accords with that found in two different strains of mice lacking PACAP (4,17). Although the response in WT mice was independent of the regime used, the PAC1 KO mice displayed different light responses at both early and late subjective night.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Using the type II procedure, we found that the response to light stimulation in PAC1 KO mice differed from our previously obtained results using the type I regime (11). Most striking was the attenuated phase delay found in the type II at early night (increased in type I), a result, however, which accords with that found in two different strains of mice lacking PACAP (4,17). Although the response in WT mice was independent of the regime used, the PAC1 KO mice displayed different light responses at both early and late subjective night.…”
Section: Discussionsupporting
confidence: 61%
“…In the first study by Kawaguchi et al (17), mice lacking PACAP showed a slightly diminished phase delay but a significantly attenuated phase advance to a single light pulse at early and late night, respectively. In a later study by Colwell et al (4), PACAP-deficient mice exhibited significant impairment in the magnitude of both light-induced phase delay and phase advance (4). We found that the PAC1 receptor-deficient mice displayed a larger phase delay at early night and decreased phase advance at late night (11).…”
supporting
confidence: 59%
See 3 more Smart Citations